Spectral and Lattice Parameters of Transition Metal Complexes of Polydentate Schiff Bases Derived from3-Formyl 4-Hydroxy Coumarin and 4-Amino phenol/2-Amino benzoic acid - JOSEPH, JOJO; MEHTA, B.H. (Asian Journal of Chemistry, 2010)
Metal(II) complexes of type M(L1)2.nH2O and M(L2)2.nH2O [where M = Mn(ll), Co(II), Ni(II), Cu(II), L1 = Schiff base derived from 3-formyl-4-hydroxy coumarin and 4-amino phenol, L2 = Schiff base derived from 3-formyl-4-hydroxy coumarin and 2-amino benzoic acid, n = 0,1,2] have been prepared and characterized by different physico-chemical methods like, IR, ESR, NMR, X-ray, UV-Vis, etc. Molar conductivity measurements indicate that the complexes are non-electrolytic in nature. Magnetic measurements and electronic spectra indicate that some complexes exhibit octahedral geometry and others exhibit square-planar geometry. The analytical data indicate that metal to ligand stoichiometry in M(L1) complexes are 1 : 2 and M(L2) complexes are 1 : 1.